Leading people - managing organizations: Contemporary public health leadership - James W. Holsinger Jr (Frontiers Research Topics, 2015)
In this Research Topic, we provide a comprehensive overview of current public health leadership research, focusing on understanding the impact of leadership on the delivery of public health services. By bringing together ground-breaking research studies detailing the development and validation of leadership activities and resources that promote effective public health practice in a variety of settings, we seek to provide a basis for leading public health organizations. We encouraged contributions that assess the effectiveness of public health leaders, as well as critical discussions of methods for improving the leadership of public health organizations at all levels. Both ongoing and completed original research was welcome, as well as methods, hypothesis and theory, and opinion papers. The effective practice of public health leadership is a key concept for public health practitioners to clearly understand as the 21st century unfolds. Following the significant lapses of leadership in the for-profit world, leaders in governmental and not-for-profit agencies are required to learn by their failed examples. A major task facing all current and prospective public health practitioners is developing the required leadership skills in order to be effective twenty first century leaders. As a consequence of the rapidly evolving health of the public, as well as the development of the discipline and practice of public health, understanding the principles and attributes of leadership are now required of all public health practitioners. Leadership can be described in a variety of ways. Leadership in public health requires skillful individuals meeting the health challenges of communities and the population as a whole. Leadership may be defined as a process that occurs whenever an individual intentionally attempts to influence another individual or group, regardless of the reason, in an effort to achieve a common goal which may or may not contribute to the success of the organization. Thus leadership is a process involving two or more people. The nature of leadership is an important aspect of the concept as a whole. Submissions relating public health leadership to the management of public health organizations were welcomed. This Research Topic provided the opportunity for authors to consider the concept of leadership from a variety of approaches. Original research papers considering a variety of leadership theories provide methodological approaches to the topic. Hypothesis and theory papers provide the basis for application of leadership to public health practice. Opinion papers provide the opportunity to develop thinking concerning practice of public health leadership.